2004
DOI: 10.1097/00004703-200402000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Parent and Teacher Agreement on Diagnosing Attention-Deficit Hyperactivity Disorder

Abstract: This study examines the impact of interrater reliability on the diagnosis of attention-deficit hyperactivity disorder (ADHD). A screening of 6171 elementary school children identified 1573 children with a high risk for ADHD according to teacher rating. Follow-up parent interviews and information from teachers were collected on 243 children. Before screening, health care professionals had diagnosed ADHD in 40% of the identified children. There was low agreement between the parent and teacher reports of ADHD sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
158
5
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(189 citation statements)
references
References 20 publications
18
158
5
3
Order By: Relevance
“…Parents were more likely to indicate that their child exhibited maladaptive behavior patterns than were teachers. This finding is consistent with previous research indicating that parents and teachers often disagree about the presence or absence of psychiatric symptoms in children (Achenbach et al, 1987;Kolko & Kazdin, 1993;Wolraich et al, 2004). Previous studies have found that parent and teacher disagreements are associated with the lack of acceptance of the child by the parents (Kolko & Kazdin, 1993) and parental stress (Youngstrom, Loeber, & Stouthamer Loeber, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Parents were more likely to indicate that their child exhibited maladaptive behavior patterns than were teachers. This finding is consistent with previous research indicating that parents and teachers often disagree about the presence or absence of psychiatric symptoms in children (Achenbach et al, 1987;Kolko & Kazdin, 1993;Wolraich et al, 2004). Previous studies have found that parent and teacher disagreements are associated with the lack of acceptance of the child by the parents (Kolko & Kazdin, 1993) and parental stress (Youngstrom, Loeber, & Stouthamer Loeber, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Wolraich et al (2004) documented poorer agreement in a clinically referred sample, especially for those children whose referral was teacher initiated (i.e. teachers were reporting children's significant symptoms and impairment, yet parents were unconcerned about their child's behaviour).…”
Section: Informant Discrepancies In the Assessment Of Adhdmentioning
confidence: 88%
“…That is, neither parents, nor teachers, consistently under or over report relative to the other. Some studies have documented that teachers have a tendency to report higher frequencies of symptoms and impairment, relative to parents, across age groups (Amador-Campos et al, 2006, Mitsis et al, 2000Wolraich et al, 2004). Others have displayed the opposite pattern in similar aged samples, with teachers under reporting relative to parents (Gomez, 2007;Malhi et al, 2008;Sollie et al, 2012).…”
Section: Informant Discrepancies In the Assessment Of Adhdmentioning
confidence: 99%
“…Identifying and controlling the modifiable risk factors of ADHD is of public health importance given the substantial burden on the quality of life of affected children and their families; the large number of children treated with stimulant medication; and the strain on medical, educational and social resources (6). Identifying risk factors for ADHD diagnosis, can inform screening, monitoring and treatment by mental health professionals, paediatricians and preschool and school staff at an age when these efforts may be maximally effective (7).…”
Section: Introductionmentioning
confidence: 99%